Association Between Water Intake and Mortality Risk—Evidence From a National Prospective Study - Zhou, Hao-long; Wei, Mu-hong; Cui, Yuan; Di, Dong-sheng; Song, Wen-jing; Zhang, Ru-yi; Liu, Jun-an; Wang, Qi (Frontiers in Nutrition, 2022)
Background: Few studies have explored the associations between water intake and mortality risk, and findings were inconsistent. Objective: This study aimed to explore the water intake-mortality association utilizing data from the National Health and Nutrition Examination Survey (NHANES) and the 2015 public linked mortality files released by the National Center for Health Statistics. Methods: We used diet- and mortality-linked data of a total of 35 463 adults (17 234 men) aged ≥ 20 years in the NHANESs 1999–2014 to perform a prospective study. Multivariate adjusted Cox proportional hazards model was used to explore the associations of the amount of water intake (expressed by total water, plain water, beverage and food water) and water intake proportion (expressed by the percentage of each kind of water) with mortality risks due to all causes, malignant neoplasms/cancer and heart disease. Restricted cubic spline plots were adopted to clarify the dose-response relationships among them. Results: With a median of 88 months (interquartile range: 49–136 months) follow-up, a total of 4915 all-cause deaths occurred, including 1073 and 861 deaths from malignant neoplasms/cancer and heart disease, respectively. The amount of water intake in either type was negatively associated with all-cause mortality risk. And negative linear dose-response relationships of water intake and all-cause mortality risk were found for all types of water except for food water, whose followed a non-linear pattern. Similarly, compared to the lowest quartile (beverage water intake: < 676 g/day; food water intake: < 532 g/day), beverage and food water intake in the range of 1033–1524 g/day and 1612–3802 g/day were associated with decreased malignant neoplasms/cancer mortality risk. A U-shaped dose-response relationship was found for beverage water intake and malignant neoplasms/cancer mortality risk and a negative linear dose-response relationship was found for food water intake and malignant neoplasms/cancer mortality risk. Coffee and/or tea consumption was/were negatively associated with mortality risks due to all causes and malignant neoplasms/cancer. No significant associations of water intake proportion and mortality risks were found. Conclusion: Our findings demonstrated that higher water intake associated with lower mortality risks among the U.S. population.